Maternal Health Phone Line: Saving Women in Papua New Guinea - Watson, Amanda H.A. (J Pers Med, 2015)
This paper presents the findings of a research project which has involved the establishment of a maternal health phone line in Milne Bay Province of Papua New Guinea (PNG). Mobile phones and landline phones are key information and communication technologies (ICTs). This research study uses the “ICTs for healthcare development” model to ascertain benefits and barriers to the successful implementation of the Childbirth Emergency Phone. PNG has a very high maternal mortality rate. The “three stages of delay” typology was developed by Thaddeus and Maine to determine factors that might delay provision of appropriate medical treatment and hence increase risk of maternal death. The “three stages of delay” typology has been utilised in various developing countries and also in the present study. Research undertaken has involved semi-structured interviews with health workers, both in rural settings and in the labour ward in Alotau. Additional data has been gathered through focus groups with health workers, analysis of notes made during phone calls, interviews with women and community leaders, observations and field visits. One hundred percent of interviewees (n = 42) said the project helped to solve communication barriers between rural health workers and Alotau Provincial Hospital. Specific examples in which the phone line has helped to create positive health outcomes will be outlined in the paper, drawn from research interviews. The Childbirth Emergency Phone project has shown itself to play a critical role in enabling healthcare workers to address life-threatening childbirth complications. The project shows potential for rollout across PNG; potentially reducing maternal morbidity and maternal mortality rates by overcoming communication challenges.